Peningkatan Keterampilan Pengelolaan Kelas Guru Baru Matematika di SLTP - Titik Sugiarti (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
Improvement of Skills in Classroom Management for the New Mathematics Teacher in the Junior High School. This study was an effort to improve teacher's skill in classroom management. It was a two-cycle classroom action research involving the new mathematics teacher at the SLTP I Jember. Using a descriptive qualitative analysis on the results of observation and interview, it could be concluded that the new mathematics teacher's skill in creating, keeping and recovering the optimum learning condition seemed to be improved. The result suggests that this classroom action research can be used as supervision model by the school principal. When a trouble cannot be solved by the teacher, he needs to cooperate with another teacher, counselor, school principal, and the Parent Teacher Association (PTA).